HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN TINGKAT KECEMASAN KELUARGA - Rina Loriana; Hilda Hilda (Poltekkes Kemenkes Kalimantan Timur, 2018)
Objective: This study aims to determine the relationship between therapeutic communication of nurses and the emotional level of patients in the ICU Hospital A.M. Parikesit Tenggarong. Method: this study is a reporting study with a cross sectional study approach. Determination of samples based on inclusion criteria until the minimum number of samples is met, using Purposive sampling. The sample opened 53 people. Instrument in the form of a questionnaire sheet about the implementation of nurse communication and clear family level. Academic level questionnaire with standard Hamilton Rating Scale for Anxiety (HRS-A). Data were analyzed using chi square. Results: From the results of the study obtained p = 0.035, it can be concluded that there is a relationship between therapeutic communication of nurses with problems related to ICU AM Parikesit Tenggarong Hospital ICU, Odss Ratio (OR) = 3.974, meaning nurses whose therapeutic communication is not good, has 4 times chance to form a patient's family while having a relationship with a nurse who has good therapeutic communication. Conclusion: There is a therapeutic communication relationship between nurses and problems related to the ICU Hospital of A.M Parikesit Tenggarong Hospital.